Case report: Myocarditis in congenital STAT1 gain-of function - Staels, Frederik; Roosens, Willem; Giovannozzi, Simone; Moens, Leen; Bogaert, Jan; Iglesias-Herrero, Cecilia; Gijsbers, Rik; Bossuyt, Xavier; Frans, Glynis; Liston, Adrian; Humblet-Baron, Stephanie; Meyts, Isabelle; et al. (Frontiers in Immunology, 2023)
Autosomal dominant Signal transducer and activator of transcription 1 (STAT1) gain-of-function (GOF) mutations result in an inborn error of immunity characterized by chronic mucocutaneous candidiasis, recurrent viral and bacterial infections, and diverse autoimmune manifestations. Current treatment consists of chronic antifungal therapy, antibiotics for concomitant infections, and immunosuppressive therapy in case of autoimmune diseases. More recently, treatment with Janus kinases 1 and 2 (JAK1/2) inhibitors have shown promising yet variable results. We describe a STAT1 GOF patient with an incidental finding of elevated cardiac troponins, leading to a diagnosis of a longstanding, slowly progressive idiopathic myocarditis, attributed to STAT1 GOF. Treatment with a JAK-inhibitor (baricitinib) mitigated cardiac inflammation on MRI but was unable to alter fibrosis, possibly due to the diagnostic and therapeutic delay, which finally led to fatal arrhythmia. Our case illustrates that myocarditis could be part of the heterogeneous disease spectrum of STAT1 GOF. Given the insidious presentation in our case, a low threshold for cardiac evaluation in STAT1 GOF patients seems warranted.